2012
DOI: 10.1614/ipsm-d-12-00014.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil–Occupancy Effects of Invasive and Native Grassland Plant Species on Composition and Diversity of Mycorrhizal Associations

Abstract: Diversified grasslands that contain native plant species can produce biofuels, support sustainable grazing systems, and produce other ecosystem services. However, ecosystem service production can be disrupted by invasion of exotic perennial plants, and these plants can have soil-microbial “legacies” that may interfere with establishment and maintenance of diversified grasslands even after effective management of the invasive species. The nature of such legacies is not well understood, but may involve suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…These studies show higher impacts with time since invasion, with the exception of one study that found the impact of an invasive plant was eroded over time by soil pathogens (Dostál et al 2013) ( Table 2). Higher ecological impacts over time may be attributable to a lag time in observed effects in recently invaded areas (Crooks 2005) or legacy effects of early invaders at older, more established sites (Grove et al 2012, Jordan et al 2012). In addition, subtle ecosystem-level impacts such as changes to soil characteristics may accrue over time, such that the extent of the impact may not be observed for decades; such long-term cumulative impacts are generally caused by ecosystem engineers (see Crooks 2002, Strayer et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show higher impacts with time since invasion, with the exception of one study that found the impact of an invasive plant was eroded over time by soil pathogens (Dostál et al 2013) ( Table 2). Higher ecological impacts over time may be attributable to a lag time in observed effects in recently invaded areas (Crooks 2005) or legacy effects of early invaders at older, more established sites (Grove et al 2012, Jordan et al 2012). In addition, subtle ecosystem-level impacts such as changes to soil characteristics may accrue over time, such that the extent of the impact may not be observed for decades; such long-term cumulative impacts are generally caused by ecosystem engineers (see Crooks 2002, Strayer et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that roots of native species had higher (Jordan et al 2012) or lower (Lekberg et al 2013) AMF richness than these of the invaders. By contrast, the composition of AMF colonizers was significantly different between invasive and native hosts, but no effect of plant origin was detected for the AMF diversity in our study, indicating the invaders, as the native plant species, might have also benefited from a substantial number of AMF taxa for thriving in the salt-stressed ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, knowledge about AMF diversity of plant species in salt-affected ecosystems remains insufficient, and the environmental constraints and host effects in saline ecosystems have yet to be investigated. The AMF communities of plants from different origins (Greipsson and DiTommaso 2006;Moora et al 2011;Jordan et al 2012;Lekberg et al 2013) and life style Lugo et al 2012;Torrecillas et al 2012) have been investigated, but again, little is known about the effect of the origin and life style of plant species on AMF diversity and community in salt-stressed ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the relationship between invasive species and environmental factors will help to elucidate invasion mechanisms. Human disturbance, temperature, latitude, soil properties, soil microorganisms, and various environmental factors may be associated with biological invasion [12][13][14][15][16]. Latitude strongly affects the distribution pattern of invasive plants in China at the provincial scale [17].…”
mentioning
confidence: 99%
“…Although numerous studies have documented the relationship between plant invasion and soil properties [5,15,[27][28][29], little attention has been paid to understanding how soil properties affect the distribution of A. philoxeroides and whether such abiotic factors are scale-dependent. The aim of our work was to explore the environmental factors that influence the distribution of A. philoxeroides in the main rivers around Nansi Lake at two different scales (river scale and plot scale).…”
mentioning
confidence: 99%